Cooperation of Electronic Preparation Systems and Financial Preparation Systems in Economic Subjects in the Republic of Uzbekistan - N., Abdieva; U., Perdebaeva (Research Parks Publishing LLC, 2022)
The article studies the directions of electronic delivery and preparation of financial accounting, automation of accounting and information flows on accounting accounts.